Respuesta :

ktreyb
x² - 14x + 33 = 0 is in the form ax² + bx + c = 0. We will need this for the second step.

Subtract 33 from both sides
x² - 14x = - 33

Divide the b term by 2 and then square the result. Then add that to both sides.
- 14 / 2 is - 7. (- 7)² = 49. Add that to both sides

x² - 14x + 49 = - 33 + 49

Combine the constants and factor the trinomial
(x - 7)² = 16

Square root both sides
x - 7 = +/- 4
or
x - 7 = - 4 and x - 7 = 4

You have to place a plus-minus statement because (- 4)² and 4² both equal 16. 

Now we solve for x in each equation. Add 7 to both sides to isolate our variable.
x = 3 and x = 11

ACCESS MORE